1997
DOI: 10.1097/00006123-199705000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Outcome, Cost Analysis, and Long-term Follow-up in Preterm Infants with Massive Grade IV Germinal Matrix Hemorrhage and Progressive Hydrocephalus

Abstract: As we have previously reported, logistic regression analysis determined that grade of hemorrhage was the only significant predictor of cognitive and motor outcomes. Most premature neonates with massive intracranial hemorrhages do not survive. The outcomes in those who do is very poor and the cost so high that we suggest that until therapeutic intervention exhibits efficacy, the consideration of withdrawal of life support should be presented as an option to the parents of these unfortunate children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 29 publications
2
27
1
Order By: Relevance
“…The use of a subcutaneous reservoir for repeated CSF tapping is also proposed as a temporary measure to alleviate PHH, allowing the use of intrathecal drugs. This technique is also associated with a high infection rate in premature infants [18]and does not allow shunt independence [19]. In situ fibrinolysis through a subcutaneous reservoir has been proposed as an alternative method, but it does not appear to represent a convincing alternative to CSF drainage for PHH [20]and is associated with a significant rate of complications [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of a subcutaneous reservoir for repeated CSF tapping is also proposed as a temporary measure to alleviate PHH, allowing the use of intrathecal drugs. This technique is also associated with a high infection rate in premature infants [18]and does not allow shunt independence [19]. In situ fibrinolysis through a subcutaneous reservoir has been proposed as an alternative method, but it does not appear to represent a convincing alternative to CSF drainage for PHH [20]and is associated with a significant rate of complications [21].…”
Section: Discussionmentioning
confidence: 99%
“…The indications for shunting are debated; some authors consider that progressive macrocrania is a prerequisite for surgery [9, 15], but Gurtner et al [15]have also indicated that most patients with progressive ventriculomegaly eventually develop macrocrania. For others, decision making is based on the progression of ventricular size rather than head circumference [13, 19]. In premature infants, hydrocephalus may lead to brain atrophy in the absence of macrocrania, and we rely more on repeated ultrasonography than head circumference for the surgical decision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations